Kinematic differences between professionals and young players in the tennis serve - Mourtzios, C.; Athanailidis, I.; Kellis, E.; Arvanitidou, V. (Coaching and Sport Science Review, 2021)
The aim of the present study was to measure and examine the differences in lower limb kinematics between the flat, slice and topspin serves, in the kinematic features of the lower limbs, at two different times of the service movement, maximum knee bending and point of contact of the racket with the ball, in 12 young tennis athletes, aged 12-16 years and in 12 professional players that they were playing on the main draw of Roland Garros. The results showed no significant differences in time between the three types of service in young athletes. Comparing the time of young athletes 34.56ms with the time of high level athletes with 30.67ms, the results showed that the professionals performed the service faster than the young athletes having a significant difference.